2013
DOI: 10.1002/ajh.23530
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in obese and overweight acute myeloid leukemia patients receiving chemotherapy dosed according to actual body weight

Abstract: Cytotoxic chemotherapy dosages are traditionally calculated according to body surface area (BSA). No guidelines exist for chemotherapy dosing of acute myeloid leukemia (AML) patients at extremes of weight. We investigated the efficacy and safety of chemotherapy dosed according to BSA based on actual body weight (ABW) among under/normal weight, overweight, and obese AML patients. AML patients (excluding acute promyelocytic leukemia) treated with anthracycline and cytarabine-based remission induction chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 21 publications
2
43
3
Order By: Relevance
“…Data from preclinical (36) and limited clinical settings (37,38) suggest pharmacokinetic variation in the metabolism of common chemotherapy agents in the obese, yet prospective trials have found no such differences by BMI (9) or in those dosed with actual compared with ideal body weight (39)(40)(41). Other hypotheses focus on the effects of obesity on both the leukemia microenvironment and the host.…”
Section: Discussionmentioning
confidence: 99%
“…Data from preclinical (36) and limited clinical settings (37,38) suggest pharmacokinetic variation in the metabolism of common chemotherapy agents in the obese, yet prospective trials have found no such differences by BMI (9) or in those dosed with actual compared with ideal body weight (39)(40)(41). Other hypotheses focus on the effects of obesity on both the leukemia microenvironment and the host.…”
Section: Discussionmentioning
confidence: 99%
“…In AML, a first study addressing this question included 21 obese patients, and those who received a dose adjustment had a lower CR rate, while toxicity did not differ between patients [6]. Finally, a recent study revealed that outcomes and toxicities in AML patients treated with ABW based chemotherapy doses did not differ according to BMI [14].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, we surprisingly found a trend for being overweight at diagnosis being associated with superior outcome in children aged 10-17 years [unrelated to t(8;21) status], similar to what has been reported in adults with AML. [40][41][42] The effect of being overweight in the oldest children with AML may be more similar to the effect of being overweight in adults. In addition, the overweight group may have benefitted from the therapy without dose reductions.…”
Section: A B C Dmentioning
confidence: 99%